Longitudinal changes in cardiac mIBG scintigraphy in mild cognitive impairment with Lewy bodies - Gemma Greenfinch; Calum A. Hamilton; Paul C. Donaghy; Michael Firbank; Nicola A. Barnett; Louise Allan; George S. Petrides; John-Paul Taylor; John T. O'Brien; Alan J. Thomas (BJPsych Open)
The aim of this study was to determine whether there was a significant change in cardiac [123I]-metaiodobenzylguanidine uptake between baseline and follow-up in individuals with mild cognitive impairment with Lewy bodies (MCI-LB) who had normal baseline scans. Eight participants with a diagnosis of probable MCI-LB and a normal baseline scan consented to a follow-up scan between 2 and 4 years after baseline. All eight repeat scans remained normal; however, in three cases uptake decreased by more than 10%. The mean change in uptake between baseline and repeat was −5.2% (range: −23.8% to +7.0%). The interpolated mean annual change in uptake was −1.6%.